Effects of heterologous platelet-rich plasma on liver enzymes, oxidative stress biomarkers and pancreatic microarchitecture in diabetic mice - Amin Arif; Muddasir H. Abbasi; Muhammad B. Khawar; Nadeem Sheikh (Kuwait Journal of Science)
Diabetes Mellitus (DM) is a chronic metabolic disorder associated with inflammation and oxidative stress. Platelet-rich plasma (PRP) has an established role in alleviating DM. The current study aimed to evaluate the effect of heterologous PRP on liver functioning, oxidative stress, and microarchitecture of pancreatic islets in diabetic mice. Twenty-four (24) healthy male (4–5 weeks old) albino mice were selected and grouped as G1, G2, G3, and G4 (n ​= ​6). G1 was control group and remained untreated while G2 (PRP group) was given a subcutaneous dose of PRP (0.5 ​mL/kg body weight) twice a week for four weeks. G3 and G4 were first given a single dose of alloxan intraperitoneally (150 ​mg/kg) to induce diabetes. PRP treatment (0.5 ​mL/kg body weight) was given to G4 only for four weeks (twice a week). Completion of experimentation was followed by blood collection through the retro-orbital puncture and dissection for pancreas excision. Sera were isolated and liver functioning and oxidative stress were assessed. ALT (P ​= ​0.0022) and AST (P ​= ​0.0010) level were found higher in G3 compared to control (G1). Conversely, PRP treatment reduced it significantly in G4. MDA (P ​< ​0.0001) and GSH (P ​< ​0.0001) also showed a statistically significant difference while CAT (P ​= ​0.5288) showed no significant difference among all groups. Furthermore, histological analyses revealed the deformation in the microarchitecture of the pancreas in G3 as it displayed vacuolated cytoplasm, damaged islets, and collagen deposition. PRP treatment restored the islets as it was observed in G4. Results revealed that PRP restored transaminases and oxidative stress biomarkers in DM and ameliorate pancreatic microarchitecture.